2013
DOI: 10.1080/01690965.2012.668197
|View full text |Cite
|
Sign up to set email alerts
|

Processing contextual and lexical cues to focus: Evidence from eye movements in reading

Abstract: Three eye movement experiments investigated the interaction between contextual and lexical focus cues during reading. Context was used to focus on either the indirect or direct object of a double object construction, which was followed by a remnant continuation that formed either a congruous or incongruous contrast with the contextually-focused object. Experiment 1 demonstrated that remnants were more difficult to process when incongruous with the contextually-focused constituent, indicating that context was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…This is based on the expectation that if participants compute the relevant focal meaning component by the time they encounter the replacives, they would find them incongruous if they are mismatched. They found that the position of only evoked the expected focus effect on-line (see also Sauermann et al, 2013 ). This, however, manifested itself in longer reading times for the postreplacive region, rather than the replacive region itself.…”
Section: Introductionmentioning
confidence: 91%
“…This is based on the expectation that if participants compute the relevant focal meaning component by the time they encounter the replacives, they would find them incongruous if they are mismatched. They found that the position of only evoked the expected focus effect on-line (see also Sauermann et al, 2013 ). This, however, manifested itself in longer reading times for the postreplacive region, rather than the replacive region itself.…”
Section: Introductionmentioning
confidence: 91%
“…Linguistic focus directs subjects' attention toward particularly salient or important discourse referents during sentence processing. Studies such as Perfetti and Goldman (1974), Greene et al (1992), Almor (1999), Foraker and McElree (2007) and Sauermann et al (2013) have explored the effects of linguistic focus on subjects' processing of coreference. Greene et al (1992) offer a model of pronoun resolution within a rich discourse representation that recognizes syntactic, semantic, and pragmatic factors for referent focus.…”
Section: Linguistic Focus and Coreference Resolutionmentioning
confidence: 99%
“…Linguistic focus directs subjects' attention toward particularly salient or important discourse referents during sentence processing. Studies such as Perfetti and Goldman (1974), Greene et al (1992), Almor (1999), Foraker and McElree (2007) and Sauermann et al (2013) have explored the effects of linguistic focus on subjects' processing of coreference. Greene et al (1992) offer a model of pronoun resolution within a rich discourse representation that recognizes syntactic, semantic, and pragmatic factors for referent focus.…”
Section: Linguistic Focus and Coreference Resolutionmentioning
confidence: 99%